336 Thromboembolic event and it's management in a girl with restrictive cardiomyopathy and implanted Berlin Heart Excor device. (11th October 2021) - Šestan, Mario; Matković, Hana; Dessardo, Sandro; Matić, Toni; Cvitković, Miran; Galić, Slobodan; Bartoniček, Dorotea; Radoš, Marko; Ozretić, David; Jovanović, Ivan; Rubić, Filip
Abstract : Ventricular assist devices are increasingly used as an emerging therapy in children with different heart condition, mostly cardiomyopathy. Introduction of pulsatile devices for bridge to heart transplantation contributed to significant improvements in the survival and discharge rate of these patients. Berlin Heart EXCOR Pediatric (BH) is a pulsatile device with different chamber sizes and is registered for use in pediatric patients. When such devices are used during longer period of time, many complications can occur, most of which are linked to clotting disorders. Therefore, Edmonton protocol was introduced for patients on BH where detailed instructions are given regarding institution and maintenance of anticoagulation and antiaggregation therapy. Despite proper management, patients could have devastating complications, particularly cerebral arterial thromboses. We present a case of a 2, 5-year-old girl who was diagnosed with restrictive cardiomyopathy caused by the p.Arg192Cys variant in the gene encoding cardiac troponin I (TNNI3). When her condition worsened and end-stage heart failure developed, she was placed on Venoarterial extracorporeal membrane oxygenation (VA-ECMO), by which she was supported for 3 weeks. Since she did not tolerate separation from mechanical support, a left ventricular assist device BH was implanted. Afterwards her anticoagulation and antiaggregation therapy was managed according Edmonton protocol thus she was given warfarin (target INR 2.8-3.5), acetylsalicylic acid (target value of ASPI test <30 U) and clopidogrel (target value of ADP test <50 U). After 50 days on BH significant changes in behavior with a qualitative change in the level of consciousness were observed in our patient prompting a computed tomographic cerebral angiography to be performed, resulting in the detection of a thrombus in the right middle cerebral artery. Motor deficit i.e. paresis of her left limbs was not present during the first hours of symptom development and appeared soon after brain imaging was done. After urgent consultation with our interventional radiologists, she underwent thrombectomy through her right femoral artery with complete reperfusion of the affected parts of the brain followed by immediate recovery of her mental state while her motor deficit resolved over the next 2 weeks. Clinicians should have a low threshold for early imaging of central nervous system when arterial thromboses are suspected. Good cooperation with radiologists that can perform such minimally invasive procedures is of the most importance since it can be lifesaving.